Acquired Localized Hypertrichosis Induced by Rivastigmine - Adrian Imbernón-Moya; Sebastian Podlipnik; Fernando Burgos; Elena Vargas-Laguna; Antonio Aguilar-Martínez; Eva Fernández-Cogolludo; Miguel Angel Gallego-Valdes (Hindawi Limited, 2016)
Hypertrichosis is the excessive hair growth in any area of the skin surface. Acquired localized hypertrichosis may be secondary to multiple causes and there is a secondary form due to several drugs, which is usually reversible with discontinuation of the causative agent. Rivastigmine is a reversible and competitive inhibitor of acetylcholinesterase and butyrylcholinesterase used for symptomatic treatment of Alzheimer dementia and Parkinson's disease. It has an adequate safety profile and cutaneous side effects are unusual. Irritant contact dermatitis, allergic dermatitis, baboon syndrome, and cutaneous rash due to rivastigmine have been reported. We report on a Caucasian 80-year-old male with personal history of Alzheimer's disease. The patient started therapy with oral rivastigmine one month prior to clinical presentation of localized hypertrichosis on both forearms. Norgalanthamine has been shown to promote hair growth activity via the proliferation of dermal papilla. Acetylcholinesterase inhibitors can induce hair growth.